1999
DOI: 10.1111/j.1471-0528.1999.tb08428.x
|View full text |Cite
|
Sign up to set email alerts
|

Two dosing regimens for preinduction cervical priming with intravaginal dinoprostone pessary: a randomised clinical trial

Abstract: Objective To compare the efficacy within 24 hours of a three-times-a-day intensive dosing regimen with a standard once daily dosing regimen using dinoprostone vaginal pessary in preinduction cervical priming.Design Randomised controlled trial.Setting Department of Obstetrics and Gynaecology, Singapore General Hospital.Participants One hundred singleton term primigravidae with cephalic presentation with unfavourable cervical scores (Bishop score 1 5 ) requiring induction of labour.Methods Eligible women were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Although we were not able to demonstrate overall cost savings attributable to IMN, we did find that women receiving IMN spent less time in the prenatal assessment ward, and this accounted for the largest cost difference between the trial groups. Similar to our findings, another study of women receiving intensive dose vaginal dinoprostone in pre-induction cervical priming has shown shortening of the period of pre-labour hospital stay for women 22 although no cost-effectiveness analysis was performed. Higher doses of IMN administered on an outpatient (at home) basis might have an even greater effect on reducing prenatal assessment ward stay, although this has yet to be investigated.…”
Section: Discussionsupporting
confidence: 82%
“…Although we were not able to demonstrate overall cost savings attributable to IMN, we did find that women receiving IMN spent less time in the prenatal assessment ward, and this accounted for the largest cost difference between the trial groups. Similar to our findings, another study of women receiving intensive dose vaginal dinoprostone in pre-induction cervical priming has shown shortening of the period of pre-labour hospital stay for women 22 although no cost-effectiveness analysis was performed. Higher doses of IMN administered on an outpatient (at home) basis might have an even greater effect on reducing prenatal assessment ward stay, although this has yet to be investigated.…”
Section: Discussionsupporting
confidence: 82%
“…Rowlands et al also reported recently that 66% of women had their cervix successful ripen by one dose of dinoprostone (5). On the contrary, Tan and Tay found that only 42% of women achieved a favorable cervical score after a single dose of vaginal prostaglandin E 2 (4). This is probably because of the difference in the initial cervical score before ripening.…”
Section: Discussionmentioning
confidence: 98%
“…When the cervix is unripe, induction is more likely to be successful if vaginal prostaglandin E 2 is used for cervical priming rather than induction by amniotomy and intravenous oxytocin infusion alone (3). However, only 40–66% of primiparous women with unfavorable cervical status had their cervices ripened successfully by a single dose of vaginal prostaglandin E 2 (4,5). Although repeated doses of prostaglandin are commonly administered in these circumstances, the value of using multiple doses of prostaglandin for cervical ripening remains controversial, as does the maximal number of doses (4,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, vaginal prostaglandin E2 (Dinoprostone, Prostin®) [4,5] has been used extensively as the preferred way for induction by most specialized institutions and is considered to be the safest option for the mother and neonate as well as the most effective one to induce vaginal delivery within 24 hours for women with an unfavorable cervix [6][7][8][9][10][11]. However, there is no full agreement on the ideal dosage of PGE2 that should be used to achieve the optimal outcome [12][13][14]. Moreover, there is much de-bate concerning the frequency of PGE2 use, whether there are different regimens for multiparous women [15], and at what point induction of labor has failed and that a cesarean section should be the exclusive and definitive mode of delivery.…”
Section: Introductionmentioning
confidence: 99%